2004
DOI: 10.1152/ajpgi.00382.2003
|View full text |Cite
|
Sign up to set email alerts
|

ICC pacing mechanisms in intact mouse intestine differ from those in cultured or dissected intestine

Abstract: Pacing of mouse intestine is driven by spontaneous activity of a network of interstitial cells of Cajal in the myenteric plexus (ICC-MP). So far, highly dissected circular muscle (CM) strips from control and mutant mice lacking ICC-MP and isolated, cultured ICC from newborn control mice were used to analyze its properties. Using intact circular and longitudinal segments of intestine, we recently reported that there were both significant similarities and differences between pacing studied in segments and from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…These results are consistent with previous observations in GBSM cells (24,29) and other visceral smooth muscle cells (9,42). The time-dependent decreases of these events caused by prolonged exposure (not significant) are similar to the observations on slow waves in the small intestine (4,19); however, unlike in the gallbladder, SERCA pump inhibitors did not cause a transient augmentation of slow wave action potential in the small intestine (17) and inhibited slow waves and spontaneous transient depolarizations in the guinea pig gastric pylorus (36,37).…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous observations in GBSM cells (24,29) and other visceral smooth muscle cells (9,42). The time-dependent decreases of these events caused by prolonged exposure (not significant) are similar to the observations on slow waves in the small intestine (4,19); however, unlike in the gallbladder, SERCA pump inhibitors did not cause a transient augmentation of slow wave action potential in the small intestine (17) and inhibited slow waves and spontaneous transient depolarizations in the guinea pig gastric pylorus (36,37).…”
Section: Discussionsupporting
confidence: 93%
“…For example, the K ϩ channels play a key role in maintaining the RMP of the gut smooth muscle cells. The alterations in calcium release by IP 3 receptors also lead to suppression or loss of slow-wave activity (16,42,99,158). The only sure way to determine that the circular smooth muscle cells do not generate spontaneous slow waves is to record from them with microelectrodes in intact W/W v or Sl/Sl mice or the Ws/Ws rats.…”
Section: The Roles Of Icc In the Generation And Propagation Of Slow Wmentioning
confidence: 99%
“…The role of the gap junctions, one of the critical components of the pacemaker hypothesis, has been questioned (12,16,40,142). The disruption of the gap junctions by pharmacological agents has little effect on the slow-wave activity in the circular muscle cells of intact muscle strips (40,43,142).…”
Section: The Roles Of Icc In the Generation And Propagation Of Slow Wmentioning
confidence: 99%
“…Among these are 1) LM pacing is faster than in the CM and is increased by TTX and L-NNA in CM, not LM; 2) robust pacing is present in the LM of w/w v mice, which lack ICC of the myenteric plexus (32); and 3) differences occur in the effects of agents such as SNP and forskolin (3,13). In the present study, electron microscopic examination of the CM layer of the Cav1 Ϫ/Ϫ mouse small intestine showed that, unlike LM, they retained some caveolar structures that were in the outer CM layer but not the inner CM layer.…”
Section: Discussionmentioning
confidence: 99%